Fast like a girl : a woman's guide to using the healing power of fasting to burn fat, boost energy, and balance hormones - Pelz, Mindy (Hay House, 2022)
"A go-to fasting manual created specifically to address women's needs based on their hormones and menstrual cycle ... Includes a 30-day fasting reset that uses the power of your cycle - even if you no longer have one!"--